Morphological and Biochemical Features Affecting the Antithrombotic Properties of the Aorta in Adult Rabbits and Rabbit Pups - Nitschmann, E.; Berry, L.; Bridge, S.; Hatton, M. W. C.; Richardson, M.; Monagle, P.; Chan, A. K. C.; Andrew, M. (Thrombosis and Haemostasis, 1998)
We hypothesised that there are important physiologic differences in arterial wall structure and function with respect to antithrombotic activity in the very young (pre-puberty) compared to adults. Electron microscopy, gel electrophoresis, and activity assays were used to examine differences in aorta structure and function comparing prepubertal rabbits (pups) to adult rabbits. Differences in endothelial function, extracellular matrix structure, proteoglycan (PG) distribution and glycosaminoglycan (GAG) content and function were shown. In both intima and media, total PG, chondroitin sulfate (CS) PG and heparan sulfate (HS) PG content were significantly increased in pups compared to adult rabbits. These findings corresponded to increased concentrations by mass analyses of CS GAG and DS GAG in aortas from pups. There was also a significant increase in antithrombin activity in pups due to HS GAG. In conclusion, differences in both structure and antithrombin activity of aortas from pups compared to adult rabbits suggest that young arteries may have greater antithrombotic potential that is, at least in part, related to increased HS GAG.